Generalized Hypergeometric Functions & Meijer G -Function - 16.6 Transformations of Variable

From testwiki
Revision as of 17:18, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
16.6.E1 F 2 3 ( a , b , c a - b + 1 , a - c + 1 ; z ) = ( 1 - z ) - a F 2 3 ( a - b - c + 1 , 1 2 a , 1 2 ( a + 1 ) a - b + 1 , a - c + 1 ; - 4 z ( 1 - z ) 2 ) Gauss-hypergeometric-pFq 3 2 𝑎 𝑏 𝑐 𝑎 𝑏 1 𝑎 𝑐 1 𝑧 superscript 1 𝑧 𝑎 Gauss-hypergeometric-pFq 3 2 𝑎 𝑏 𝑐 1 1 2 𝑎 1 2 𝑎 1 𝑎 𝑏 1 𝑎 𝑐 1 4 𝑧 superscript 1 𝑧 2 {\displaystyle{\displaystyle{{}_{3}F_{2}}\left({a,b,c\atop a-b+1,a-c+1};z% \right)=(1-z)^{-a}{{}_{3}F_{2}}\left({a-b-c+1,\frac{1}{2}a,\frac{1}{2}(a+1)% \atop a-b+1,a-c+1};\frac{-4z}{(1-z)^{2}}\right)}}
\genhyperF{3}{2}@@{a,b,c}{a-b+1,a-c+1}{z} = (1-z)^{-a}\genhyperF{3}{2}@@{a-b-c+1,\frac{1}{2}a,\frac{1}{2}(a+1)}{a-b+1,a-c+1}{\frac{-4z}{(1-z)^{2}}}

hypergeom([a , b , c], [a - b + 1 , a - c + 1], z) = (1 - z)^(- a)* hypergeom([a - b - c + 1 ,(1)/(2)*a ,(1)/(2)*(a + 1)], [a - b + 1 , a - c + 1], (- 4*z)/((1 - z)^(2)))
HypergeometricPFQ[{a , b , c}, {a - b + 1 , a - c + 1}, z] == (1 - z)^(- a)* HypergeometricPFQ[{a - b - c + 1 ,Divide[1,2]*a ,Divide[1,2]*(a + 1)}, {a - b + 1 , a - c + 1}, Divide[- 4*z,(1 - z)^(2)]]
Failure Failure
Failed [258 / 300]
Result: -2.076719790+.860205503*I
Test Values: {a = -3/2, b = -3/2, c = -3/2, z = 1/2*3^(1/2)+1/2*I}

Result: -1.428233246+.1e-8*I
Test Values: {a = -3/2, b = -3/2, c = -3/2, z = 1/2-1/2*I*3^(1/2)}

... skip entries to safe data
Skipped - Because timed out
16.6.E2 F 2 3 ( a , 2 b - a - 1 , 2 - 2 b + a b , a - b + 3 2 ; z 4 ) = ( 1 - z ) - a F 2 3 ( 1 3 a , 1 3 a + 1 3 , 1 3 a + 2 3 b , a - b + 3 2 ; - 27 z 4 ( 1 - z ) 3 ) Gauss-hypergeometric-pFq 3 2 𝑎 2 𝑏 𝑎 1 2 2 𝑏 𝑎 𝑏 𝑎 𝑏 3 2 𝑧 4 superscript 1 𝑧 𝑎 Gauss-hypergeometric-pFq 3 2 1 3 𝑎 1 3 𝑎 1 3 1 3 𝑎 2 3 𝑏 𝑎 𝑏 3 2 27 𝑧 4 superscript 1 𝑧 3 {\displaystyle{\displaystyle{{}_{3}F_{2}}\left({a,2b-a-1,2-2b+a\atop b,a-b+% \frac{3}{2}};\frac{z}{4}\right)=(1-z)^{-a}{{}_{3}F_{2}}\left({\frac{1}{3}a,% \frac{1}{3}a+\frac{1}{3},\frac{1}{3}a+\frac{2}{3}\atop b,a-b+\frac{3}{2}};% \frac{-27z}{4(1-z)^{3}}\right)}}
\genhyperF{3}{2}@@{a,2b-a-1,2-2b+a}{b,a-b+\frac{3}{2}}{\frac{z}{4}} = (1-z)^{-a}\genhyperF{3}{2}@@{\frac{1}{3}a,\frac{1}{3}a+\frac{1}{3},\frac{1}{3}a+\frac{2}{3}}{b,a-b+\frac{3}{2}}{\frac{-27z}{4(1-z)^{3}}}

hypergeom([a , 2*b - a - 1 , 2 - 2*b + a], [b , a - b +(3)/(2)], (z)/(4)) = (1 - z)^(- a)* hypergeom([(1)/(3)*a ,(1)/(3)*a +(1)/(3),(1)/(3)*a +(2)/(3)], [b , a - b +(3)/(2)], (- 27*z)/(4*(1 - z)^(3)))
HypergeometricPFQ[{a , 2*b - a - 1 , 2 - 2*b + a}, {b , a - b +Divide[3,2]}, Divide[z,4]] == (1 - z)^(- a)* HypergeometricPFQ[{Divide[1,3]*a ,Divide[1,3]*a +Divide[1,3],Divide[1,3]*a +Divide[2,3]}, {b , a - b +Divide[3,2]}, Divide[- 27*z,4*(1 - z)^(3)]]
Failure Failure
Failed [216 / 252]
Result: .1888061791+.200959324e-1*I
Test Values: {a = -3/2, b = -3/2, z = 1/2*3^(1/2)+1/2*I}

Result: -.140210603-.95166922e-1*I
Test Values: {a = -3/2, b = -3/2, z = -1/2+1/2*I*3^(1/2)}

... skip entries to safe data
Skipped - Because timed out